ANALYSIS OF FACTORS AND INCOME LEVELS ON LIFESTYLE BASED ON SHARIA PERSPECTIVE - Sutono Sutono (International Conference on Economic Business and Social Science, 2023)
Lifestyle is something that cannot be separated from people's lives because without realizing it, the association, environment, and habits of the people around us will greatly affect our lifestyle. The factor that greatly influences our lifestyle is income that a person has. If a person's income is large, that person can buy expensive goods compared to those who have relatively low incomes. A person's income will affect the level of consumption. The higher the income, the more goods or services it needs. Conversely, the less income, the less the amount of goods and services needed. Factors that influence lifestyle are reference groups are groups that have a direct or indirect influence on a person's attitudes and behavior, social class is a group that is relatively homogeneous and lasts a long time in a society, which is arranged in a hierarchical order, and members in each level has the same values, interests, and behavior. Two main elements in the social system of class division in society, namely position and role, culture includes knowledge, beliefs, arts, morals, laws, customs, and habits acquired by individuals as members of society. The lifestyle recommended by Rasulullah SAW is modest and simple. Modest in demeanor, and dress, and not excessive in buying food, and do not forget to set aside (give away) some of the assets we have to our less fortunate relatives. A hedonic lifestyle is something that is prohibited in Islam. If we buy clothes, we should dress neatly and naturally. If we eat, buy healthy food and just enough, don't overdo it. We are also prohibited from using anything to boast